REALISING THE POTENTIAL OF INFORMATION COMMUNICATION TECHNOLOGY (ICT) TO SUPPORT PEOPLE CHALLENGED BY ILLNESS OR DISABILITY TO MAINTAIN THEIR INDEPENDENCE - Johnston, Ian (Ревија за социјална политика/Journal of Social Policy, 2015)
This presentation charts the progress of ENS4Care, aninnovativeproject funded by the EU for 2 years from December 2013 to engagesocial and health care practitioners in collaboratively addressingchallenges arising from a rapidly ageing population in many parts ofEurope (Eurostat, 2014). Principal amongst such challenges are theincreasing numbers of people living with long-term conditions, disabilities,non-communicable diseases (NCD) and chronic diseases and thedecreasing percentage of the population active in the healthcare labourforce to manage the delivery of patient-centric care (WHO, 2010).